2022
DOI: 10.1080/20008066.2022.2138099
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for posttraumatic stress disorder in trauma-exposed individuals during the COVID-19 pandemic – findings from a pan-European study

Abstract: Background: The COVID-19 pandemic is a health emergency resulting in multiple stressors that may be related to posttraumatic stress disorder (PTSD). Objective: This study examined relationships between risk and protective factors, pandemic-related stressors, and PTSD during the COVID-19 pandemic. Methods: Data from the European Society of Traumatic Stress Studies (ESTSS) ADJUST Study were used. N = 4,607 trauma-exposed participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 44 publications
(57 reference statements)
0
15
0
4
Order By: Relevance
“…A systematic review and meta-analysis that assessed the prevalence of anxiety, depression, posttraumatic symptoms, stress, and sleep problems in the early pandemic period reported that posttraumatic stress symptoms were the most prevalent presentation in COVID-19 infected individuals, though the rates of all mental health problems among COVID-19 infected individuals were uniformly high (Dragioti et al, 2022 ). In the ADJUST study by Lotzin and colleagues ( 2022 ) published in this Special Issue, the estimated prevalence of PTSD among trauma-exposed general population adults recruited from 11 countries was 17.7%, more than twice the base rate of PTSD in the non-COVID era. Using a new assessment to identify pandemic-specific stressors, Lotzin et al ( 2022 ) found that non-modifiable risk (e.g., younger age, female sex) and modifiable risk (e.g., poor health status) and protective (e.g., social contact) factors were associated with PTSD, underlining the importance of brief early targeted interventions for both full and subclinical PTSD.…”
Section: Impact Of the Pandemic On Community Populations Students Vet...mentioning
confidence: 99%
See 3 more Smart Citations
“…A systematic review and meta-analysis that assessed the prevalence of anxiety, depression, posttraumatic symptoms, stress, and sleep problems in the early pandemic period reported that posttraumatic stress symptoms were the most prevalent presentation in COVID-19 infected individuals, though the rates of all mental health problems among COVID-19 infected individuals were uniformly high (Dragioti et al, 2022 ). In the ADJUST study by Lotzin and colleagues ( 2022 ) published in this Special Issue, the estimated prevalence of PTSD among trauma-exposed general population adults recruited from 11 countries was 17.7%, more than twice the base rate of PTSD in the non-COVID era. Using a new assessment to identify pandemic-specific stressors, Lotzin et al ( 2022 ) found that non-modifiable risk (e.g., younger age, female sex) and modifiable risk (e.g., poor health status) and protective (e.g., social contact) factors were associated with PTSD, underlining the importance of brief early targeted interventions for both full and subclinical PTSD.…”
Section: Impact Of the Pandemic On Community Populations Students Vet...mentioning
confidence: 99%
“…In the ADJUST study by Lotzin and colleagues ( 2022 ) published in this Special Issue, the estimated prevalence of PTSD among trauma-exposed general population adults recruited from 11 countries was 17.7%, more than twice the base rate of PTSD in the non-COVID era. Using a new assessment to identify pandemic-specific stressors, Lotzin et al ( 2022 ) found that non-modifiable risk (e.g., younger age, female sex) and modifiable risk (e.g., poor health status) and protective (e.g., social contact) factors were associated with PTSD, underlining the importance of brief early targeted interventions for both full and subclinical PTSD. While this cross-sectional study could not support causal inferences on vulnerability and protective factors, it highlights touchpoints for future mental health pandemic preparedness with respect to screening and early intervention (Lotzin et al, 2021 ).…”
Section: Impact Of the Pandemic On Community Populations Students Vet...mentioning
confidence: 99%
See 2 more Smart Citations
“…The year 2022 might be characterized by cascading and intersecting crises that culminated in traumatic stress for billions of individuals worldwide. While the COVID-19 pandemic still has an impact on the mental health of children and adults in large parts of the world (e.g., BinDhim et al, 2021 ; Lotzin et al, 2022 ; Olff et al, 2021 ; Richardson et al, 2022 ; Vasileva et al, 2021 ), 2022 will be remembered as the year of the Russian invasion in Ukraine. It has caused unimaginable amounts of traumatic stress in the people directly affected and among all age groups and genders in Europe and around the world (e.g., Schwartz et al, 2022 ).…”
Section: Crisis After Crisismentioning
confidence: 99%